STUDY ON TRANSLATION ACCURACY OF INTERROGATIVE SENTENCES IN THE SUBTITLE OF WANDAVISION SERIES - Melissa Lydia; Mawarta Onida Sinaga; Ina Sukaesih (Politeknik Negeri Jakarta, 2024)
In the global movie industry, subtitles are essential as they bridge the communication between the story of a movie and the global audiences. Therefore, subtitling translators must provide accurate translations of subtitles so that the audience can understand the story of a movie. This descriptive-qualitative research aims to analyze the types of interrogative sentences, translation techniques, and the accuracy of the interrogative sentences’ translations in the subtitles of the first two episodes of the Wanda Vision series through content analysis and focus group discussion. The results of this study found 130 data classify into 3 types of interrogative sentences based on Quirk et al. (1985): Yes-no questions, WH questions, and Alternative Questions. In translating these interrogative sentences, there are 12 Molina and Albir’s translation techniques used by the translator, with three dominant techniques as follows: established equivalent, reduction, and literal translation. The average accuracy of the translation of interrogative sentences is 2.69 that if reviewed based on the accuracy parameters by Nababan (2012), this score indicates that interrogative sentences in this study overall have been translated quite accurately